Coke oven top anti-erosion castable

By using coke oven top erosion-resistant castable materials made of high-aluminum bauxite fine powder, electromelted mullite and other raw materials, the problem that traditional materials are difficult to meet long-term use needs when facing chemical erosion and thermal shock is achieved. It has excellent corrosion resistance and construction convenience, and meets the requirements of green and environmental protection.

CN119390430AInactive Publication Date: 2025-02-07YIXING WEIJIE REFRACTORY MATERIALS CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411722786.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-02-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional coke oven top refractory materials are difficult to meet the needs of long-term use when facing strong chemical erosion and thermal shock, and the preparation process is complex and costly, which limits its wide application in modern high-efficiency coke ovens.

Method used

The coke oven furnace top anti-erosion castable material is made of high-alumina bauxite fine powder, electromelting mullite, high-temperature cement, water, waste brick particles, fillers, hardener and dispersant as raw materials. By optimizing the raw material ratio and The particle size distribution improves the thermal shock resistance, acid resistance and construction convenience of the castable material.

Benefits of technology

It realizes excellent corrosion resistance, good construction properties and high density of the top materials of the coke oven, reduces the firing process, meets the requirements of green and environmental protection, and has adjustable shape, good sealing effect, high strength, and good thermal shock stability. Features.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005158468330000121
    Figure BDA0005158468330000121
Patent Text Reader

Abstract

The invention relates to the technical field of castable, and particularly discloses anti-erosion castable for a coke oven top. The anti-erosion castable for the coke oven top is prepared from the following raw materials in parts by weight: 30 to 34 parts of high bauxite fine powder, 38 to 42 parts of electric smelting mullite, 10 to 15 parts of high-temperature cement, 8 to 14 parts of water, 6 to 10 parts of waste brick particles, 6 to 10 parts of filler, 2 to 5 parts of hardening accelerator and 0.3 to 0.8 part of dispersing agent. According to the invention, links such as firing are reduced, the construction is convenient, the overall stability is good, the obtained coke oven top anti-erosion castable has no weak parts such as brick joints, the sealing effect is good, the product shape can be adjusted, the strength is high, the thermal shock stability is good, and the acid gas corrosion resistance is good; the raw materials are uniformly mixed, so that the preparation method is simple in steps, low in cost, green, environment-friendly, suitable for industrial production and wide in market prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of castables, and more particularly to an anti-corrosion castable for a coke oven top. Background Art

[0002] With the development of industrial technology, the metallurgical industry has increasingly higher requirements for refractory materials, especially for the top of coke ovens working in high temperature environments, which puts forward higher standards for anti-corrosion, high temperature resistance and service life. As a key equipment in the coking process, the top area of ​​the coke oven is exposed to high temperature, corrosive gases and molten materials for a long time. Therefore, the selection of suitable refractory materials is of great significance to ensure the safe and stable operation of the coke oven. Traditional coke oven top refractory materials mostly use clay and high-alumina refractory bricks. Although they have certain high temperature resistance, they are often difficult to meet the needs of long-term use when facing strong chemical erosion and thermal shock. In addition, the preparation process of traditional materials is complicated, the cost is high, and there are great difficulties in the construction process, which limits its wide application in modern high-efficiency coke ovens. In summary, the development of a coke oven top castable that has both excellent anti-corrosion performance and green environmental protection is of great significance to improving the operating efficiency of coke ovens and reducing maintenance costs. Summary of the invention

[0003] In view of the deficiencies in the prior art, the present invention provides a coke oven top castable with excellent corrosion resistance, good workability, high density and environmental friendliness.

[0004] The present invention provides a coke oven top castable, which adopts the following technical solution:

[0005] A coke oven roof erosion-resistant castable comprises the following raw materials in parts by weight: 30-34 parts of high-alumina fine powder, 38-42 parts of fused mullite, 10-15 parts of high-temperature cement, 8-14 parts of water, 6-10 parts of waste brick particles, 6-10 parts of fillers, 2-5 parts of hardening accelerators and 0.3-0.8 parts of dispersants.

[0006] Preferably, the erosion-resistant castable for the coke oven roof comprises the following raw materials in parts by weight: 32 parts of high-alumina fine powder, 40 parts of fused mullite, 12 parts of high-temperature cement, 10 parts of water, 8 parts of waste brick particles, 8 parts of filler, 3 parts of hardening accelerator and 0.5 parts of dispersant.

[0007] Preferably, the filler is composed of ultrafine silicon powder and calcium hexaaluminate fine powder in a mass ratio of 1-3:1.

[0008] Preferably, the hardening accelerator is at least one of aluminum sulfate, sodium silicate and boric acid.

[0009] Preferably, the dispersant is at least one of sodium tripolyphosphate, sodium hexametaphosphate and citric acid.

[0010] Preferably, the particle size of the ultrafine silicon powder is 0.014-0.048 mm, and the particle size of the calcium hexaaluminate fine powder is 0.063-0.088 mm.

[0011] Preferably, the high-alumina fine powder is a mixture of high-alumina fine powders of three different particle sizes: 0.1-0.125 mm, 0.15-0.21 mm, and 0.25-0.5 mm.

[0012] Preferably, the fused mullite is composed of coarse-grained fused mullite with a particle size of 1.2-5 mm, which accounts for 60% to 70% of the total fused mullite, and fine-grained fused mullite with a particle size of 0.075-1 mm, which accounts for 30% to 40% of the total fused mullite; the particle size of the waste brick particles is 0.085-2 mm.

[0013] Preferably, the method for preparing the erosion-resistant castable for the coke oven roof comprises the following steps:

[0014] S1. According to the weight parts, weigh high-alumina bauxite fine powder, fused mullite, high-temperature cement, water, waste brick particles, filler, hardening accelerator and dispersant for use;

[0015] S2, stirring high-alumina bauxite fine powder, fused mullite, high-temperature cement, waste brick particles and fillers until they are evenly mixed, adding pre-weighed water, dispersant and hardening accelerator, and continuing to stir until all ingredients are completely mixed to form a uniform slurry;

[0016] S3. Pour the slurry into a mold, remove bubbles, and take it out after standing at room temperature for 20-48 hours. After preliminary hardening, cure it at 20-25°C and a relative humidity of more than 90% for 24-72 hours, and then keep it at 110-200°C for 12-36 hours to obtain the anti-corrosion castable for the coke oven roof.

[0017] In summary, the present invention has the following beneficial effects:

[0018] 1. The anti-corrosion castable for the coke oven roof of the present invention is made of high-alumina bauxite fine powder, fused mullite, high-temperature cement, water, waste brick particles, fillers, hardening accelerators and dispersants as raw materials. The components complement each other, the construction is convenient, the overall stability is excellent, the firing process is reduced, and it meets the requirements of green environmental protection. The anti-corrosion castable for the coke oven roof has the characteristics of adjustable shape, and there is no weak part such as brick seams, good sealing effect, high strength, good thermal shock stability, and excellent tolerance to acidic gas corrosion.

[0019] 2. The present invention utilizes the excellent thermal shock resistance and acid resistance of high-alumina bauxite fine powder and fused mullite to effectively reduce cracks caused by rapid temperature changes, endow the castable with excellent acid gas corrosion resistance, and ensure that it can be used stably for a long time in a corrosive environment. By accurately controlling the particle size distribution of high-alumina bauxite fine powder and fused mullite, a multi-particle size combination is formed to improve the uniformity, density and structural stability of the castable, thereby reducing the penetration channel of acid gas; in terms of filler, it is composed of ultrafine silicon micropowder with a particle size of 0.014-0.048mm and calcium hexaaluminate fine powder with a particle size of 0.063-0.088mm in a mass ratio. The combination of the two can not only fill the gaps between the particles, but also enhance the high temperature stability and corrosion resistance of the castable; in addition, the use of dispersants and hardening accelerators improves the fluidity and uniformity of the castable, while reducing bubbles and pores, accelerating the hydration reaction process, thereby shortening the curing time. DETAILED DESCRIPTION

[0020] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0021] Unless otherwise specified, the materials, reagents, etc. used in the examples and comparative examples of the present invention can be obtained from commercial sources.

[0022] Example 1

[0023] The present embodiment provides an anti-corrosion castable for a coke oven roof, comprising the following raw materials in parts by weight: 30 parts of high-alumina bauxite fine powder, 38 parts of fused mullite, 10 parts of high-temperature cement, 8 parts of water, 6 parts of waste brick particles, 6 parts of filler, 2 parts of aluminum sulfate and 0.3 parts of sodium tripolyphosphate, wherein the high-alumina bauxite fine powder is a mixture of high-alumina bauxite fine powders of three different particle sizes, 0.1 mm, 0.5 mm and 0.25 mm, with a mass ratio of 4:1:1, the fused mullite is composed of coarse-grained fused mullite with a particle size of 1.2 mm, which accounts for 60% of the total amount of the fused mullite, and fine-grained fused mullite with a particle size of 0.075 mm, which accounts for 40% of the total amount of the fused mullite, the particle size of the waste brick particles is 0.085 mm, and the filler is composed of ultrafine silicon powder with a particle size of 0.014 mm and calcium hexaaluminate fine powder with a particle size of 0.063 mm, with a mass ratio of 1:1.

[0024] A coke oven top erosion-resistant castable is prepared by the following method:

[0025] S1. According to the weight parts, weigh high-alumina bauxite fine powder, fused mullite, high-temperature cement, water, waste brick particles, filler, aluminum sulfate and sodium tripolyphosphate for later use;

[0026] S2, high alumina fine powder, fused mullite, high temperature cement, waste brick particles and filler are stirred at a speed of 150r / min for 10min to obtain a mixture, and pre-weighed water, dispersant and hardening accelerator are added, and stirred at a speed of 200r / min for 20min to form a uniform castable;

[0027] S3. Pour the slurry into a mold, remove bubbles, and take it out after standing at room temperature for 20 hours. After preliminary hardening, cure it at 20°C and 90% relative humidity for 24 hours and then keep it at 110°C for 36 hours to obtain the anti-corrosion castable for the coke oven roof.

[0028] Example 2

[0029] The present embodiment provides an anti-corrosion castable for a coke oven roof, comprising the following raw materials in parts by weight: 31 parts of high-alumina bauxite fine powder, 39 parts of fused mullite, 11 parts of high-temperature cement, 9 parts of water, 7 parts of waste brick particles, 7 parts of filler, 3 parts of sodium silicate and 0.4 parts of sodium hexametaphosphate, wherein the high-alumina bauxite fine powder is a mixture of high-alumina bauxite fine powders of three different particle sizes, 0.11 mm, 0.16 mm and 0.3 mm, with a mass ratio of 5:2:1, the fused mullite is composed of coarse-grained fused mullite with a particle size of 1.4 mm, which accounts for 62% of the total amount of the fused mullite, and fine-grained fused mullite with a particle size of 0.08 mm, which accounts for 38% of the total amount of the fused mullite, the particle size of the waste brick particles is 0.09 mm, and the filler is composed of ultrafine silicon powder with a particle size of 0.05 mm and calcium hexaaluminate fine powder with a particle size of 0.069 mm, with a mass ratio of 2:1.

[0030] A coke oven top erosion-resistant castable is prepared by the following method:

[0031] S1. According to the weight parts, weigh high-alumina bauxite fine powder, fused mullite, high-temperature cement, water, waste brick particles, filler, sodium silicate and sodium hexametaphosphate for later use;

[0032] S2, high alumina fine powder, fused mullite, high temperature cement, waste brick particles and filler are stirred at a speed of 200 r / min for 8 minutes to obtain a mixture, and pre-weighed water, dispersant and hardening accelerator are added, and stirred at a speed of 220 r / min for 18 minutes to form a uniform casting material;

[0033] S3. Pour the slurry into a mold, remove bubbles, let it stand at room temperature for 30 hours, then take it out. After preliminary hardening, cure it at 22°C and 92% relative humidity for 65 hours, and then keep it at 120°C for 30 hours to obtain the anti-corrosion castable for the coke oven roof.

[0034] Example 3

[0035] The present embodiment provides an anti-corrosion castable for a coke oven roof, comprising the following raw materials in parts by weight: 33 parts of high-alumina bauxite fine powder, 41 parts of fused mullite, 13 parts of high-temperature cement, 13 parts of water, 9 parts of waste brick particles, 10 parts of filler, 4 parts of aluminum sulfate and 0.8 parts of sodium hexametaphosphate, wherein the high-alumina bauxite fine powder is a mixture of high-alumina bauxite fine powders of three different particle sizes, 0.123 mm, 0.18 mm and 0.4 mm, with a mass ratio of 5:3:1, the fused mullite is composed of coarse-grained fused mullite with a particle size of 3 mm, which accounts for 68% of the total amount of the fused mullite, and fine-grained fused mullite with a particle size of 0.08 mm, which accounts for 32% of the total amount of the fused mullite, the particle size of the waste brick particles is 1 mm, and the filler is composed of ultrafine silicon powder with a particle size of 0.03 mm and calcium hexaaluminate fine powder with a particle size of 0.07 mm, with a mass ratio of 2:1.

[0036] A coke oven top erosion-resistant castable is prepared by the following method:

[0037] S1. According to the weight parts, weigh high-alumina bauxite fine powder, fused mullite, high-temperature cement, water, waste brick particles, filler, aluminum sulfate and sodium hexametaphosphate for later use;

[0038] S2, high alumina fine powder, fused mullite, high temperature cement, waste brick particles and filler are stirred at a speed of 280r / min for 7min to obtain a mixture, and pre-weighed water, dispersant and hardening accelerator are added, and stirred at a speed of 280r / min for 12min to form a uniform castable;

[0039] S3. Pour the slurry into a mold, remove bubbles, let it stand at room temperature for 30 hours, then take it out. After preliminary hardening, cure it at 22°C and 92% relative humidity for 65 hours, and then keep it at 120°C for 30 hours to obtain the anti-corrosion castable for the coke oven roof.

[0040] Example 4

[0041] The present embodiment provides an anti-corrosion castable for a coke oven roof, comprising the following raw materials in parts by weight: 32 parts of high-alumina bauxite fine powder, 40 parts of fused mullite, 12 parts of high-temperature cement, 10 parts of water, 8 parts of waste brick particles, 8 parts of filler, 3 parts of aluminum sulfate and 0.5 parts of sodium tripolyphosphate, wherein the high-alumina bauxite fine powder is a mixture of high-alumina bauxite fine powders of three different particle sizes of 0.125 mm, 0.21 mm and 0.5 mm, and the mass ratio thereof is 6:3:1; the fused mullite is composed of coarse-grained fused mullite with a particle size of 5 mm, which accounts for 70% of the total amount of the fused mullite, and fine-grained fused mullite with a particle size of 0.09 mm, which accounts for 30% of the total amount of the fused mullite; the particle size of the waste brick particles is 1.0 mm; and the filler is composed of ultrafine silicon powder with a particle size of 0.045 mm and calcium hexaaluminate fine powder with a particle size of 0.075 mm, and the mass ratio thereof is 3:1.

[0042] A coke oven top erosion-resistant castable is prepared by the following method:

[0043] S1. According to the weight parts, weigh high-alumina bauxite fine powder, fused mullite, high-temperature cement, water, waste brick particles, filler, aluminum sulfate and sodium tripolyphosphate for later use;

[0044] S2, high alumina fine powder, fused mullite, high temperature cement, waste brick particles and filler are stirred at a speed of 300 r / min for 5 min to obtain a mixture, and pre-weighed water, dispersant and hardening accelerator are added, and stirred at a speed of 300 r / min for 10 min to form a uniform castable;

[0045] S3. Pour the slurry into a mold, remove bubbles, let it stand at room temperature for 45 hours, then take it out. After preliminary hardening, cure it at 25°C and 95% relative humidity for 72 hours, and then keep it at 180°C for 20 hours to obtain the anti-corrosion castable for the coke oven roof.

[0046] Comparative Example 1

[0047] The present embodiment provides an anti-corrosion castable for a coke oven roof, comprising the following raw materials in parts by weight: 32 parts of high-alumina bauxite fine powder, 40 parts of fused mullite, 12 parts of high-temperature cement, 10 parts of water, 8 parts of waste brick particles, 3 parts of aluminum sulfate and 0.5 parts of sodium tripolyphosphate, wherein the high-alumina bauxite fine powder is a mixture of high-alumina bauxite fine powders of three different particle sizes, 0.125 mm, 0.21 mm and 0.5 mm, with a mass ratio of 6:3:1, the fused mullite is composed of coarse-grained fused mullite with a particle size of 5 mm, which accounts for 70% of the total amount of the fused mullite, and fine-grained fused mullite with a particle size of 0.09 mm, which accounts for 30% of the total amount of the fused mullite, and the particle size of the waste brick particles is 1.0 mm.

[0048] A coke oven top erosion-resistant castable is prepared by the following method:

[0049] S1. According to the weight parts, weigh high-alumina bauxite fine powder, fused mullite, high-temperature cement, water, waste brick particles, aluminum sulfate and sodium tripolyphosphate for later use;

[0050] S2, high alumina fine powder, fused mullite, high temperature cement, waste brick particles and filler are stirred at a speed of 300 r / min for 5 min to obtain a mixture, and pre-weighed water, dispersant and hardening accelerator are added, and stirred at a speed of 300 r / min for 10 min to form a uniform castable;

[0051] S3. Pour the slurry into a mold, remove bubbles, let it stand at room temperature for 45 hours, then take it out. After preliminary hardening, cure it at 25°C and 95% relative humidity for 72 hours, and then keep it at 180°C for 20 hours to obtain the anti-corrosion castable for the coke oven roof.

[0052] Comparative Example 2

[0053] The present embodiment provides an anti-corrosion castable for a coke oven roof, comprising the following raw materials in parts by weight: 32 parts of high-alumina bauxite fine powder, 40 parts of fused mullite, 12 parts of high-temperature cement, 10 parts of water, 8 parts of waste brick particles, 8 parts of filler, 3 parts of aluminum sulfate and 0.5 parts of sodium tripolyphosphate, wherein the high-alumina bauxite fine powder is a mixture of high-alumina bauxite fine powders of three different particle sizes, 0.125 mm, 0.21 mm and 0.5 mm, with a mass ratio of 6:3:1, the fused mullite is composed of coarse-grained fused mullite with a particle size of 5 mm, which accounts for 70% of the total amount of the fused mullite, and fine-grained fused mullite with a particle size of 0.09 mm, which accounts for 30% of the total amount of the fused mullite, the particle size of the waste brick particles is 1.0 mm, and the filler is composed of ultrafine silicon powder with a particle size of 0.045 mm.

[0054] A coke oven top erosion-resistant castable is prepared by the following method:

[0055] S1. According to the weight parts, weigh high-alumina bauxite fine powder, fused mullite, high-temperature cement, water, waste brick particles, filler, aluminum sulfate and sodium tripolyphosphate for later use;

[0056] S2, high alumina fine powder, fused mullite, high temperature cement, waste brick particles and filler are stirred at a speed of 300 r / min for 5 min to obtain a mixture, and pre-weighed water, dispersant and hardening accelerator are added, and stirred at a speed of 300 r / min for 10 min to form a uniform castable;

[0057] S3. Pour the slurry into a mold, remove bubbles, let it stand at room temperature for 45 hours, then take it out. After preliminary hardening, cure it at 25°C and 95% relative humidity for 72 hours, and then keep it at 180°C for 20 hours to obtain the anti-corrosion castable for the coke oven roof.

[0058] Comparative Example 3

[0059] The present embodiment provides an anti-corrosion castable for a coke oven roof, comprising the following raw materials in parts by weight: 32 parts of high-alumina bauxite fine powder, 40 parts of fused mullite, 12 parts of high-temperature cement, 10 parts of water, 8 parts of waste brick particles, 8 parts of filler, 3 parts of aluminum sulfate and 0.5 parts of sodium tripolyphosphate, wherein the high-alumina bauxite fine powder is a mixture of high-alumina bauxite fine powders of three different particle sizes, 0.125 mm, 0.21 mm and 0.5 mm, with a mass ratio of 6:3:1, the fused mullite is composed of coarse-grained fused mullite with a particle size of 5 mm, which accounts for 70% of the total amount of the fused mullite, and fine-grained fused mullite with a particle size of 0.09 mm, which accounts for 30% of the total amount of the fused mullite, the waste brick particles have a particle size of 1.0 mm, and the filler is composed of calcium hexaaluminate fine powder with a particle size of 0.075 mm.

[0060] A coke oven top erosion-resistant castable is prepared by the following method:

[0061] S1. According to the weight parts, weigh high-alumina bauxite fine powder, fused mullite, high-temperature cement, water, waste brick particles, filler, aluminum sulfate and sodium tripolyphosphate for later use;

[0062] S2, high alumina fine powder, fused mullite, high temperature cement, waste brick particles and filler are stirred at a speed of 300 r / min for 5 min to obtain a mixture, and pre-weighed water, dispersant and hardening accelerator are added, and stirred at a speed of 300 r / min for 10 min to form a uniform castable;

[0063] S3. Pour the slurry into a mold, remove bubbles, let it stand at room temperature for 45 hours, then take it out. After preliminary hardening, cure it at 25°C and 95% relative humidity for 72 hours, and then keep it at 180°C for 20 hours to obtain the anti-corrosion castable for the coke oven roof.

[0064] Comparative Example 4

[0065] The present embodiment provides an anti-corrosion castable for a coke oven roof, comprising the following raw materials in parts by weight: 32 parts of high-alumina bauxite fine powder, 40 parts of fused mullite, 12 parts of high-temperature cement, 10 parts of water, 8 parts of waste brick particles, 8 parts of filler and 0.5 parts of sodium tripolyphosphate, wherein the high-alumina bauxite fine powder is a mixture of high-alumina bauxite fine powders of three different particle sizes of 0.125 mm, 0.21 mm and 0.5 mm, and the mass ratio thereof is 6:3:1; the fused mullite is composed of coarse-grained fused mullite with a particle size of 5 mm, which accounts for 70% of the total amount of the fused mullite, and fine-grained fused mullite with a particle size of 0.09 mm, which accounts for 30% of the total amount of the fused mullite; the particle size of the waste brick particles is 1.0 mm; and the filler is composed of ultrafine silicon powder with a particle size of 0.045 mm and calcium hexaaluminate fine powder with a particle size of 0.075 mm, and the mass ratio thereof is 3:1.

[0066] A coke oven top erosion-resistant castable is prepared by the following method:

[0067] S1. According to the weight parts, weigh high-alumina bauxite fine powder, fused mullite, high-temperature cement, water, waste brick particles, filler and sodium tripolyphosphate for later use;

[0068] S2, high alumina fine powder, fused mullite, high temperature cement, waste brick particles and filler are stirred at a speed of 300 r / min for 5 min to obtain a mixture, and pre-weighed water, dispersant and hardening accelerator are added, and stirred at a speed of 300 r / min for 10 min to form a uniform castable;

[0069] S3. Pour the slurry into a mold, remove bubbles, let it stand at room temperature for 45 hours, then take it out. After preliminary hardening, cure it at 25°C and 95% relative humidity for 72 hours, and then keep it at 180°C for 20 hours to obtain the anti-corrosion castable for the coke oven roof.

[0070] Comparative Example 5

[0071] The present embodiment provides an anti-corrosion castable for a coke oven roof, comprising the following raw materials in parts by weight: 32 parts of high-alumina fine powder, 40 parts of fused mullite, 12 parts of high-temperature cement, 10 parts of water, 8 parts of waste brick particles, 8 parts of filler, 3 parts of aluminum sulfate and 0.5 parts of sodium tripolyphosphate, wherein the high-alumina fine powder consists of high-alumina fine powder with a particle size of 0.125 mm, the fused mullite consists of coarse-grained fused mullite with a particle size of 5 mm, which accounts for 70% of the total amount of the fused mullite, and fine-grained fused mullite with a particle size of 0.09 mm, which accounts for 30% of the total amount of the fused mullite, the particle size of the waste brick particles is 1.0 mm, and the filler consists of ultrafine silicon powder with a particle size of 0.045 mm and calcium hexaaluminate fine powder with a particle size of 0.075 mm, and the mass ratio thereof is 3:1.

[0072] A coke oven top erosion-resistant castable is prepared by the following method:

[0073] S1. According to the weight parts, weigh high-alumina bauxite fine powder, fused mullite, high-temperature cement, water, waste brick particles, filler, aluminum sulfate and sodium tripolyphosphate for later use;

[0074] S2, high alumina fine powder, fused mullite, high temperature cement, waste brick particles and filler are stirred at a speed of 300 r / min for 5 min to obtain a mixture, and pre-weighed water, dispersant and hardening accelerator are added, and stirred at a speed of 300 r / min for 10 min to form a uniform castable;

[0075] S3. Pour the slurry into a mold, remove bubbles, let it stand at room temperature for 45 hours, then take it out. After preliminary hardening, cure it at 25°C and 95% relative humidity for 72 hours, and then keep it at 180°C for 20 hours to obtain the anti-corrosion castable for the coke oven roof.

[0076] Comparative Example 6

[0077] The present embodiment provides an anti-corrosion castable for a coke oven roof, comprising the following raw materials in parts by weight: 32 parts of high-alumina bauxite fine powder, 40 parts of fused mullite, 12 parts of high-temperature cement, 10 parts of water, 8 parts of waste brick particles, 8 parts of filler, 3 parts of aluminum sulfate and 0.5 parts of sodium tripolyphosphate, wherein the high-alumina bauxite fine powder is a mixture of high-alumina bauxite fine powders of three different particle sizes of 0.125 mm, 0.21 mm and 0.5 mm, and the mass ratio thereof is 6:3:1, the particle size of the fused mullite is 5 mm, the particle size of the waste brick particles is 1.0 mm, and the filler is composed of ultrafine silicon powder with a particle size of 0.045 mm and calcium hexaaluminate fine powder with a particle size of 0.075 mm, and the mass ratio thereof is 3:1.

[0078] A coke oven top erosion-resistant castable is prepared by the following method:

[0079] S1. According to the weight parts, weigh high-alumina bauxite fine powder, fused mullite, high-temperature cement, water, waste brick particles, filler, aluminum sulfate and sodium tripolyphosphate for later use;

[0080] S2, high alumina fine powder, fused mullite, high temperature cement, waste brick particles and filler are stirred at a speed of 300 r / min for 5 min to obtain a mixture, and pre-weighed water, dispersant and hardening accelerator are added, and stirred at a speed of 300 r / min for 10 min to form a uniform castable;

[0081] S3. Pour the slurry into a mold, remove bubbles, let it stand at room temperature for 45 hours, then take it out. After preliminary hardening, cure it at 25°C and 95% relative humidity for 72 hours, and then keep it at 180°C for 20 hours to obtain the anti-corrosion castable for the coke oven roof.

[0082] Performance Testing

[0083] The coke oven roof erosion resistant castables obtained in Examples 1-4 and Comparative Examples 1-6 were respectively subjected to a compressive strength test and a weight loss test after being immersed in 10% sulfuric acid and 10% sodium hydroxide for 24 hours. The compressive strength test standard is GB / T5072-1985. The test results are shown in Table 1.

[0084] Table 1

[0085]

[0086] From the results shown in Table 1 above, it can be seen that the compressive strength and acid and alkali corrosion resistance of the coke oven roof anti-corrosion castables prepared in Examples 1-4 of the present invention are much better than those in Comparative Examples 1-6.

[0087] This specific embodiment is merely an explanation of the present invention and is not a limitation of the present invention. After reading this specification, those skilled in the art may make non-creative modifications to the present embodiment as needed. However, as long as they are within the scope of the claims of the present invention, they are protected by the patent law.

Claims

1. A coke oven roof erosion resistant castable, characterized in that: The invention comprises the following raw materials in parts by weight: 30-34 parts of high-alumina fine powder, 38-42 parts of fused mullite, 10-15 parts of high-temperature cement, 8-14 parts of water, 6-10 parts of waste brick particles, 6-10 parts of fillers, 2-5 parts of hardening accelerators and 0.3-0.8 parts of dispersants.

2. The erosion-resistant castable for coke oven roof according to claim 1, characterized in that: The method comprises the following raw materials in parts by weight: 32 parts of high-alumina fine powder, 40 parts of fused mullite, 12 parts of high-temperature cement, 10 parts of water, 8 parts of waste brick particles, 8 parts of fillers, 3 parts of hardening accelerators and 0.5 parts of dispersants.

3. The erosion-resistant castable for coke oven roof according to claim 1, characterized in that: The filler is composed of ultrafine silicon powder and calcium hexaaluminate fine powder in a mass ratio of 1-3:

1.

4. The erosion-resistant castable for coke oven roof according to claim 1, characterized in that: The hardening accelerator is at least one of aluminum sulfate, sodium silicate and boric acid.

5. The erosion-resistant castable for coke oven roof according to claim 1, characterized in that: The dispersant is at least one of sodium tripolyphosphate, sodium hexametaphosphate and citric acid.

6. The erosion-resistant castable for coke oven roof according to claim 1, characterized in that: The particle size of the ultrafine silicon powder is 0.014-0.048 mm, and the particle size of the calcium hexaaluminate fine powder is 0.063-0.088 mm.

7. The erosion-resistant castable for coke oven roof according to claim 1, characterized in that: The high-alumina fine powder is prepared by mixing high-alumina fine powders of three different particle sizes: 0.1-0.125 mm, 0.15-0.21 mm and 0.25-0.5 mm.

8. The erosion-resistant castable for coke oven roof according to claim 1, characterized in that: The fused mullite is composed of coarse fused mullite with a particle size of 1.2-5 mm, which accounts for 60%-70% of the total fused mullite, and fine fused mullite with a particle size of 0.075-1 mm, which accounts for 30%-40% of the total fused mullite; the particle size of the waste brick particles is 0.085-2 mm.

9. A method for preparing the erosion-resistant castable for coke oven roof according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1. According to the weight parts, weigh high-alumina bauxite fine powder, fused mullite, high-temperature cement, water, waste brick particles, filler, hardening accelerator and dispersant for use; S2, stirring high-alumina bauxite fine powder, fused mullite, high-temperature cement, waste brick particles and fillers until they are evenly mixed, adding pre-weighed water, dispersant and hardening accelerator, and continuing to stir until all ingredients are completely mixed to form a uniform slurry; S3. Pour the slurry into a mold, remove bubbles, and take it out after standing at room temperature for 20-48 hours. After preliminary hardening, cure it in an environment of 20-25°C and 90-95% relative humidity for 24-72 hours, and then keep it warm at 110-200°C for 12-36 hours to obtain the anti-corrosion castable for the coke oven roof.

Citation Information

Patent Citations

  • Fire-resistant material coated by hot-blast valve

    CN101337823A

  • Silicon carbide mullite wear-resisting casting material

    CN103819204A

  • Anti-permeation anti-erosion molten pool castable for aluminum melting furnace

    CN104370559A

  • Lightweight mullite sagger and preparation method and application thereof

    CN112778006A

  • Alkali-resistant, wear-resistant and erosion-resistant castable and preparation method thereof

    CN117362012A